2015
DOI: 10.1371/journal.pone.0127006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Change and Fisheries Bycatch on Shy Albatross (Thalassarche cauta) in Southern Australia

Abstract: The impacts of climate change on marine species are often compounded by other stressors that make direct attribution and prediction difficult. Shy albatrosses (Thalassarche cauta) breeding on Albatross Island, Tasmania, show an unusually restricted foraging range, allowing easier discrimination between the influence of non-climate stressors (fisheries bycatch) and environmental variation. Local environmental conditions (rainfall, air temperature, and sea-surface height, an indicator of upwelling) during the vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…The main effects of fisheries on seabirds are population decreases due to incidental mortality (Rolland et al 2010, Barbraud et al 2012, Thomson et al 2015, so increases in overlap with fisheries would entail a greater risk. Our results showed that several species would overlap less in the future with highbycatch fisheries, independent of the climate change scenario.…”
Section: Species and Fisheries Overlapsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main effects of fisheries on seabirds are population decreases due to incidental mortality (Rolland et al 2010, Barbraud et al 2012, Thomson et al 2015, so increases in overlap with fisheries would entail a greater risk. Our results showed that several species would overlap less in the future with highbycatch fisheries, independent of the climate change scenario.…”
Section: Species and Fisheries Overlapsmentioning
confidence: 99%
“…Impacts include a reduction in fish populations from overfishing (Pauly et al 1998, Daskalov 2002, Scheffer et al 2005 and incidental mortality (bycatch) of non-target organisms such as seabirds, marine mammals or sea turtles (Jiménez et al 2010, Lewison et al 2014, with repercussions for food webs contributing to biodiversity loss (Pauly et al 1998, Scheffer et al 2005, Daskalov et al 2007) ecosystem simplification (Scheffer et al 2005, Möllmann et al 2008, Howarth et al 2014) and loss of ecosystem services (Worm et al 2006). Climate change and fisheries may cause synergistic effects on species and populations (Rolland et al 2010, Walther 2010, Thomson et al 2015. Bycatch in fisheries is one of the main causes for the alarming declines and high threat of extinction of albatrosses and large petrels (Croxall et al 2012), with 100 000s of birds killed annually (Anderson et al 2011(Anderson et al , Žydelis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is best assessed using integrated population models (Francis and Sagar 2011, Matthiopoulos et al 2013, Maunder and Punt 2013, Thomson et al. 2015, Tuck et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the current study show that compared to the pinkie, the sprayer and baffler reduced heavy interactions by 58.9% and 83.7% respectively, resulting in a potential reduction in seabird interactions of 90% and 96% compared to no mitigation device. Given the uptake of the bafflers and the sprayer in the CTS (about 95% of active vessels in total), it is likely the fishery has reduced bycatch beyond the predicted 50% (from 2010 levels) needed to offset losses due to potential future temperature changes (Thomson et al 2015).…”
Section: Impacts On Seabird Populationsmentioning
confidence: 99%
“…By extrapolating observer data that monitored 3.6% of the total effort in the fishery, Phillips et al (2010) estimated that from the 23 774 CTS shots (trawl sets) undertaken in 2006, there were interactions with 250 black-browed albatross Thalassarche melanophris and 861 with shy albatross T. cauta. Fishery impacts on shy albatross have been particularly highlighted through population modelling by Thomson et al (2015), who concluded that mortalities from inter action with trawl fisheries may need to be reduced by 50%, in order to offset the impacts on chick survival of the predicted increases in maximum temperatures during the chick rearing season due to climate change.…”
Section: Introductionmentioning
confidence: 99%